Review—Research Progress on Layered Transition Metal Oxide Cathode Materials for Sodium Ion Batteries. Issue 5 (14th May 2021) - Wei, Fanglin; Zhang, Qiaoping; Zhang, Peng; Tian, Wenqian; Dai, Kehua; Zhang, Liang; Mao, Jing; Shao, Guosheng
Abstract : The proportion of new energy power generation gets higher and higher, due to the depletion of fossil energy resources. However, new energy power is generally unstable, so that it is necessary to use energy storage batteries to balance the power peak and valley. Although lithium-ion batteries have been widely used in various fields, in particular for large-scale energy storage, the low abundance of lithium in the earth crust makes it untenable to meet the ever-intense future demand. Sodium ion batteries, which have similar energy storage mechanism to lithium-ion batteries, have attracted significant attentions due to their abundant raw material resources, low cost, and fairly high energy densities. Layered transition metal oxides are a class of the most promising cathode materials for sodium ion batteries, owing to their high theoretical specific capacities, good conductivity, and fast diffusion kinetics. In this paper, we conduct a comprehensive review of the electrochemical performance, structural characteristics, performance shortcomings and modification technologies about the O3- and P2-type layered transition metal oxide cathode materials. The application potentials of layered materials are summarized and analyzed, which provides a reference for the industry to select the most promising and practical layered cathode material for sodium ion batteries.